Oesophagostomy tube complications in azotaemic dogs: 139 cases (2015 to 2019). (1st December 2020) - Perondi, F.; Stefanescu, A.; Marchetti, V.; Gori, E.; Pierini, A.; Vitalaru, B. A.; Lippi, I.
Abstract : Objectives: To retrospectively assess the rate of oesophagostomy tube‐related complications in azotaemic dogs, the influence of the oesophagostomy tube (o‐tube) duration and the therapeutic approach (medical versus haemodialysis) on the complication rate. Materials and Methods: Medical records were retrospectively reviewed in order to identify azotaemic dogswhich underwent o‐tube placement. o‐Tube duration (short‐term versus long‐term), time of o‐tube change, therapeutic approach (medical versus haemodialysis), prevalence of minor (malposition, suture related, inflammation, muco‐purulent discharge, abscess) and major (haemorrhage, malposition, obstruction, dislodgement, vomiting of the tube, food coming from the stoma) o‐tube‐related complications were extracted. Univariate and multivariate logistic regression analysis were performed to identify the risk factors for o‐tube‐related complications. Results: Tube‐related complications were reported in 74 of 139 dogs (53%). Minor complications were reported in 66 of 74 (89%) and major complications in eight of 74 (11%). In azotaemic dogs, o‐tube indwelling time (odds ratio (OR) 1.03; 95% confidence interval (CI) 1.01 to 1.05), and the use of haemodialysis (OR 40.12; 95% CI 9.18 to 175.20) were risk factors for o‐tube‐related complications. Clinical Significance: The majority of o‐tube‐related complications were minor, and easily manageable, with no need of hospitalisation, tube‐removal or euthanasia. In azotaemic dogs, the use of haemodialysis was strongly associated with a higher risk of o‐tube‐related complications, possibly as a consequence of the presence of the neck bandage.